Daytime diet of the lesser sac-winged bat (Saccopteryx leptura) in a Colombian Pacific Island - Vivas-Toro, Isabela; Mendivil-Nieto, Julián Alexander (THERYA, 2022)
Insectivorous bats represent more than half of all the Chiropterans of the world. Although they are important stabilizers of insect populations within their habitat due to their feeding habits, just few studies have been focused on the diet of insular bat species. The lesser sac-winged bat, Saccopteryx leptura, is widely distributed in the new world tropics, but little is known about its prey selection. In this study we determined the diet composition of the population of S. leptura from Gorgona Island, Colombia, using stomach and intestinal content samples. We focused our research on their atypical daytime feeding behavior to evaluate differences in prey selection considering two main factors: 1) plant canopy cover and 2) bat sex. We found prey representatives of nine orders of insects, with Hymenoptera, Coleoptera and Hemiptera as the most consumed according to their abundance and volume percentage. We identified two new records at genus level in S. lepturaÂ´s diet, Camponotus (Formicidae) and Trigona (Apidae). In general terms, we did not find differences in the diet between canopy covers nor sexes. However, when analyzing the consumed percentage volume by order, there were significant differences in consumption of Psocoptera in both factors. Our results suggest that S. leptura has an opportunistic diet, as they tend to feed on prey of a wide range of sizes, usually the most abundant and available in the environment.